(untitled) (Revista Argentina de Musicología, 2024)
Some indigenous communities in Latin America have presented new musical creations based on popular genres such as rock and hip-hop. The case of rock in the Tsotsil language or bats’i rock (true rock) is particularly significant because it incorporates cultural elements such as the language, clothing, musical instruments, etc., as well as others from the global rock culture such as the song format and participation in music festivals. However, more than showing reminiscences of the traditional in the rock they produce, I am interested above all in evidencing the processes of intersubjective meaning that configure this youth music scene. This article seeks to demonstrate that the notion of “bats’i”, as a central category in the process of semiosis, evidences a new platform of enunciation in different contexts thanks to the creation of a new semiotic text materialized as bats’i rock.